Four new species of deep-water catsharks of the genus Parmaturus (Carcharhiniformes: Scyliorhinidae) from New Caledonia, Indonesia and Australia - Séret, Bernard; Last, Peter R. (Zootaxa, 2007)
Four new species of rare scyliorhinid catsharks are provisionally assigned to the genus Parmaturus: P. lanatus sp. nov. from Indonesia, P. albimarginatus sp. nov. and P. albipenis sp. nov. from northern New Caledonia, and P. bigus sp. nov. from northeastern Australia. These species differ from each other by a combination of body morphology, denticle shape, dentition, colour and vertebral counts. An identification key to the Indo–Pacific Parmaturus species is provided. Comments on the diagnostic features separating the genera Halaelurus and Parmaturus are given.